2020
DOI: 10.48132/hdbr.305
|View full text |Cite
|
Sign up to set email alerts
|

antecedents of University Students' Entrepreneurship Intention. The Theory of Planned Behaviour Viewpoint

Abstract: Finding out whether university students will take up entrepreneurship on graduation bodes well for any economy especially the developing ones. This is because it will help governments, and other stakeholders to plan better. Importantly, if university students embrace an entrepreneurial career, it will reduce unemployment and subsequently mitigate the scourge of poverty and inequality. This study was quantitative targeting university students to understand how they perceive entrepreneurship, what they think ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…People make decisions based on their attitude (Huyghe and Knockert, 2015; Ajzen, 2011). A person’s attitude may suggest that they will invest the effort required to achieve something if they have faith in their skills and know they can thrive in a creative workplace (Iwu et al ., 2020). When beginning a new business, for example, one’s ATT has a significant role in shaping their decision-making mindset (Mishra and Singh, 2022; Lihua, 2022; Acuna-Duran et al ., 2021; Boubker et al ., 2021; Su et al ., 2021; Tehseen and Haider, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…People make decisions based on their attitude (Huyghe and Knockert, 2015; Ajzen, 2011). A person’s attitude may suggest that they will invest the effort required to achieve something if they have faith in their skills and know they can thrive in a creative workplace (Iwu et al ., 2020). When beginning a new business, for example, one’s ATT has a significant role in shaping their decision-making mindset (Mishra and Singh, 2022; Lihua, 2022; Acuna-Duran et al ., 2021; Boubker et al ., 2021; Su et al ., 2021; Tehseen and Haider, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Regarding entrepreneurship, influential people like peers and role models significantly influence whether or not someone will be motivated to prepare a business plan. Students who observe role models and receive guidance and support from their family members and friends are more likely to want to be entrepreneurs (Iwu et al ., 2020). Some renowned researchers from different counties (Malaysia, Slovenia, and China) found that SUBNs directly affect EI (Wu and Tian, 2022; Velástegui and Chacón, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This ultimately helps with being able to make business decisions and contribute to the economy (Bakheet, 2018) . The study by Iwu et al (2020) also examined students’ perceptions of entrepreneurship in relation to their career intentions. However, they argued that successful entrepreneurs are not necessarily trained in entrepreneurship and the program of study does not play an important role in developing the entrepreneurial mindset.…”
Section: Literature Reviewmentioning
confidence: 99%